The Influence of Service, Price, and Promotion on Online Transportation User Decisions in Medan - Rahmat Alamsyah Harahap; Eszra Nicolas Sibarani; Melisa Romaito Siahaan; Riris Victoria M Pangaribuan; Frida T Telaumbanua (International Journal of Health and Pharmaceutical (IJHP), 2026)
Online transportation first became popular in Indonesia with the arrival of Gojek in 2010. There are several online transportation services available in Medan, such as Grab, Gojek, Maxim, and InDrive. Service issues include inconsistency in service delivery, drivers who are unfriendly and unprofessional. Pricing issues include price differences between application platforms and complex fare structures. Promotional issues include excessive reliance on promotions to attract new users and a lack of user education on promotions in payment methods. Quantitative descriptive research is the research method, and explanatory research is the nature of the research. Interviews, questionnaires, and documentation studies are the data collection methods. Multiple linear regression with classical assumption testing, namely normality, multicollinearity, and heteroscedasticity, is the method of analysis. The research population consists of 300 users, 171 of whom were selected through simple random sampling divided into 21 sub-districts in Medan, and the validity and reliability were tested on 30 of them. The simultaneous effect of service, price, and promotion (F-test) has a positive effect on the success rate. Fcount 34.524 > Ftable 2.66 with sig. 0.000 < 0.05. Partially (t-test), service tcount 4.883 > ttable 1.65392 and sig. 0.000 < 0.05, price tcount 1.494 < ttable 1.65392 and sig. 0.137 > 0.05, promotion tcount 1.769 > ttable 1.65392 and sig. 0.079 > 0.05. The adjusted Rsquare coefficient test result is 0.372, meaning that 37.2% of the decision to use online transportation services in Medan is influenced by service, price, and promotion, while the remaining 62.8% is explained by other factors.